2018
DOI: 10.1038/s41389-018-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lncRNA MIR222HG co-transcribed from the miR-221/222 gene promoter facilitates the development of castration-resistant prostate cancer

Abstract: Mechanisms by which non-coding RNAs contribute to the progression of hormone-sensitive prostate cancer (PCa) (HSPC) to castration-resistant PCa (CRPC) remain largely unknown. We previously showed that microRNA-221/222 is up-regulated in CRPC and plays a critical role in modulating androgen receptor function during CRPC development. With further investigation, we characterized a putative promoter region located 23.3 kb upstream of the miR-221/222 gene, and this promoter is differentially activated in CRPC LNCaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Functionally, miR-221 targeted HECTD2 and RAB1A in castration-resistant LNCaP subclones, which modulates androgen receptor-mediated signaling and favors the progression to a castration-resistant state [14]. With this in view, miR-221/miR-222 overexpression as part of an escape from VEGFR2 inhibition could be well in line with publications demonstrating oncogenic roles of miR-221 and miR-222 in PCa cells [13][14][15][16].…”
Section: Mir-221 Upregulation As Part Of a Sunitinib Escape Mechanismsupporting
confidence: 73%
See 1 more Smart Citation
“…Functionally, miR-221 targeted HECTD2 and RAB1A in castration-resistant LNCaP subclones, which modulates androgen receptor-mediated signaling and favors the progression to a castration-resistant state [14]. With this in view, miR-221/miR-222 overexpression as part of an escape from VEGFR2 inhibition could be well in line with publications demonstrating oncogenic roles of miR-221 and miR-222 in PCa cells [13][14][15][16].…”
Section: Mir-221 Upregulation As Part Of a Sunitinib Escape Mechanismsupporting
confidence: 73%
“…On a molecular basis, there are conflicting data regarding miR-221-3p function in PCa cells. While our group could show that restoration of miR-221-3p expression had a tumour suppressive role in castration-resistant DU145 and PC3 cells [12], other researchers demonstrated that miR-221-3p also acted as an oncogene in LNCaP and PC3 cells by supporting progress to a castration-resistant state [13][14][15][16].…”
Section: Introductionmentioning
confidence: 64%
“…As a class of novel regulatory RNAs, lncRNAs are revealed to have various roles in PCa [50][51][52][53][54]. LncRNA TMPO-AS1 is reported to promote PCa cell proliferation and migration [50].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA LINC00844 prevents PCa cell migration 10 Arch Med Sci and invasion via facilitating androgen receptor binding to the chromatin [52]. LncRNA MIR222HG facilitates PCa development via affecting miR-NAs-mediated expression silencing [53]. LncRNA SChLAP1 promotes aggressive PCa via antagonizing the SWI/SNF complex [54].…”
Section: Discussionmentioning
confidence: 99%
“…So far, various lncRNA has been reported to involved in the pathogenesis of PCa, such as SNHG7, MIR222HG, PVT1, and HOTAIR . The dysregulated lncRNAs allows us to identify the mechanism clearly, and also provide help for the further PCa therapy.…”
Section: Discussionmentioning
confidence: 99%